The influence of the discovery learning model with differentiated learning on the HOTS learning outcomes - Setyo Rini, Daniar; Rusdi, Rusdi; Nurlaela, Siti (STKIP Persada Khatulistiwa Sintang, 2025)
Higher-Order Thinking Skills (HOTS) is an important competency of the 21st century; yet, HOTS among high school students in Indonesia remains relatively low. This study aims to determine the effect of the discovery learning model with differentiated learning on the HOTS learning outcomes of high school students on the subject of motion systems. The research method employed was quantitative, utilizing a quasi-experimental design. The sample consists of two class XI Moving Biology classes from SMAN 61 Jakarta, selected through cluster random sampling, each consisting of 30 students. The research instrument consisted of a HOTS test with 13 essay questions covering cognitive levels C4 (analyzing), C5 (evaluating), and C6 (creating), an observation sheet, and a learning style questionnaire. The research results showed that the average posttest score of the experimental class (67.53) was higher compared to the control class (55.30). The t-test on the gain score showed a significant difference between the two classes. This study concludes that the discovery learning model with a differentiated learning approach has a significant effect on the HOTS learning outcomes of high school students on the topic of motion systems.